URGENSI ULUM Al-HADIS DALAM MEMAHAMI Al-QUR’AN DAN STATUS HADIS - Kamaruddin, Kamaruddin (Hunafa: Jurnal Studia Islamika, 2005)
This article discusses functions of hadith to Qur’an. It elucidates role of hadis in elaborating meanings contained in Qur’an. It is found that there are some functions of hadith to Qur’an such as bayan al-tafsir (exegesing commentary), bayan al-tauqid (conforming commentary), bayan al-tahqiq (inquiring commentary) and bayan al-tasyri (law-enacting commentary). This article also suggests role of ulum al-hadith in investigating hadith validity level. Kata Kunci: Ulum al-Hadis, Al-Qur’an, Hadis